Theoretical Bases for the Study of Speech Changes in the State of Anxiety - Turchak, Olesia (Psychological Prospects Journal, 2014)
At the present stage of social development in terms of active growth of life pace, production and interpersonal contacts, people must be able to work effectively in different psychological conditions, under stress and emotional tension. Stressful situations cause changes in human activities, including speech changes. Thus, the problem of individual peculiarities of human speech in stressful situations is a key issue of psychological science and requires a comprehensive study. This article is devoted to the study of empirical referents of human speech changes, which are influenced by anxiety. The author examines the state of anxiety as an emotional state of acute anxiety associated in the mind of the individual to the prediction of failure, danger or expectation of something important, meaningful to a person under the circumstances of uncertainty. To understand how anxiety affects the state of human speech, the author analyzes the theoretical sources of the problem of verbal expressions of anxiety and anxiety manifestations in writing. As a result of the research, the author distinguishes the following empirical referents of speech changes, caused by the state of anxiety: problems in word choice; grammatical changes; changes in motor implementation of expression; self-corrections. The article also defines the theoretical principles of studying of speech parameter changes both, in oral and written speeches in a state of anxiety. In the future, empirical indicators proposed by the author, can be used in studying of human activity in emotiogenic situations.